POPULATION PHARMACOKINETICS - RAMESH N; SOCORRINA COLACO; KOUMARAVEL; KUMAR EP (International Journal of Pharma and Bio Sciences, 2010)
The current interest in population pharmacokinetics stems from the concern that the pharmacokinetics of new drugs are not studied in relevant populations, that is, patients likely to receive the drug at an early enough stage in the drug's development. The obvious time to collect pharmacokinetic information on the target population is during large-scale clinical trials carried out during phase III and post marketing surveillance of the drug development programme. Population pharmacokinetics has emerged as a key role in clinical pharmacology to study drug use by designing rational dosage forms and dosage regimes. Quantitative representation of the dose-concentrationresponse relationship should provide information for prediction of the level of response to a certain level of drug dose. Several mathematical approaches describe the dose-concentration-response relationships. Depending on the single dose or the steady-state measurements carried out, clinical significance of estimated parameters will be valuable when underlying physiologic processes (disease, age, gender, etc.) are considered. The purpose of this review article is to describe the significance of population pharmacokinetics i.e. variability of drug disposition between individuals.